Medical care of patients with Wilson disease in Germany: a multidisciplinary survey among university centers - Zimny, Sebastian Raphael; Bourhis, Hélène; Weber, Sabine; Reiter, Florian Paul; Hohenester, Simon; Kraft, Eduard; Mohr, Isabelle; Merle, Uta; Weiss, Karl Heinz; Denk, Gerald (Orphanet journal of rare diseases, 2023)
Wilson disease (WD) is a rare, hereditary disorder of copper metabolism. Due to its variable symptoms and manifestations, diagnosis remains challenging. Affected patients must obtain lifelong medical treatment, as the disease is fatal if untreated. Patients require continuous monitoring, but little is known about the care of these patients in Germany. Therefore, we analyzed the medical care of WD patients at German university centers. We sent a questionnaire containing 20 questions to a total of 108 departments of pediatrics, neurology and gastroenterology in 36 university hospitals. Our questions referred to the characteristics of WD patients at the different sites and internal procedures regarding diagnosis, therapy and follow-up. A descriptive statistical analysis was performed.